2020
DOI: 10.3390/ijerph17228407
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perspective on Strategies to Reduce Sedentary Behavior in Educational Institutions

Abstract: Standing desks and physical activity breaks can counteract the negative consequences of sedentarism at school. However, the implementation of these strategies should not restrict the pedagogical process. The aim of this study was to assess teachers’ perspectives on strategies to reduce sedentary behavior (SB) of students in the classroom. An online survey was conducted, and the answers were analyzed using descriptive statistics and frequency distribution. The relationships between the variables were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As suggested by several authors, adjustable school furniture (chairs and/or desks) can prevent poor posture and ensure the well-being of students in the classroom [ 47, 50, 51 ]. Previous research has suggested adjustable school furniture solutions [ 52, 53 ], while its regular use in Slovenian schools is not yet common [ 15 ]. Thus, further development and effort are needed to achieve long-term implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by several authors, adjustable school furniture (chairs and/or desks) can prevent poor posture and ensure the well-being of students in the classroom [ 47, 50, 51 ]. Previous research has suggested adjustable school furniture solutions [ 52, 53 ], while its regular use in Slovenian schools is not yet common [ 15 ]. Thus, further development and effort are needed to achieve long-term implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Unsuitable school desk is associated with neck and shoulder pain while too low backrest might be one of the factors influencing lower back pain [ 13, 14 ]. Awkward body posture of students, resulting from inappropriate school furniture, might also affect students’ attention and creativity [ 15 ]. On the other hand, if the students are using a more suitable school furniture, better academic performance can be achieved and musculoskeletal disorders can be reduced [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another surveyed teachers to understand their perceptions of using standing desks and activity breaks in primary/secondary school and university settings. [ 16 ]. Whilst there were concerns the desks could increase class disruption, most teachers believed standing desks and physical activity breaks were feasible in the classroom setting.…”
Section: Introductionmentioning
confidence: 99%
“…Published reports of teachers’ perspectives of various in-classroom movement programmes have mainly been conducted in developed countries such as the USA [ 19 ], UK [ 20 ], Canada [ 21 ], Ireland [ 22 ], and Slovenia [ 23 ]. In general, these studies report a relatively positive attitude, and a wide-range in-classroom movement strategies being used by teachers.…”
Section: Introductionmentioning
confidence: 99%